BIOMEDICAL, ECOSOCIAL, AND EDUCATIONAL APPROACHES TO BIOLOGICAL CONTROL OF MOSQUITO LARVAL HABITATS IN VULNERABLE COMMUNITIES: A COMPREHENSIVE MODEL FOR PREVENTION AND COMMUNITY HEALTH - Edison Pasca; Ysaías Alvarado (REDIELUZ, 2025)
This research explores the biological control of mosquitoes through a multidisciplinary approach, combining biomedical, eco-social, and educational perspectives, with a focus on vulnerable communi- ties. The primary objective is to examine how bio- logical strategies, including the utilization of natu- ral predators and ecological methods, can curb the proliferation of mosquitoes and the diseases they transmit, while fostering community education for the effective management of larval habitats. The methodology employed is a documentary review, which compiles previous studies on biological con- trol in various regions, evaluating its effectiveness and applicability in areas with limited resources. The results show that biological methods, such as the use of predatory fish and copepods, are more sustainable and less costly than insecticides, with a lower environmental impact. Additionally, the im- portance of community education and participation in managing mosquito breeding sites is emphasi- zed. The conclusions highlight the necessity of a comprehensive approach that integrates biological control, public policies, and educational strategies to address public health challenges in vulnerable communities. This ecological and participatory approach is key to the sustainability and effective- ness of interventions, ensuring lasting and accessi- ble control.